Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations Colonel Wake's resignation of the Chairmanship was deeply regretted by workers and patients alike — he has been the mainstay of the Clinic — but we are fortunate in still having his keen interest and sympathy. We are very grateful to Mr. Capener for his address to the representatives, which aroused keen interest and was a real stimulus to further activity in the villages. Toc H have again to be thanked for their organisation of transport and the car owners for their willing and unfailing help. The V.A.D.'s have been most unflagging in their attendance, and consider it a great privilege to be asked to help. E.M. WATERWORTH, Hon. Sec. TORQUAY ORTHOPAEDIC CLINIC. The year 1932 has been a very busy one. The work has steadily increased. This increase has definitely justified our holding two Surgeon's sessions a month, instead of one as previously. This arrangement began towards the end of last year and is much appreciated by the patients and by those members of the medical profession who take advantage of the service offered by the Association. In the early autumn it was found essential to have two After-Care Sisters attending weekly. This has overcome the previous unavoidable waiting on the part of the patients and their friends and made the work much easier for the Clinic Staff and transport workers. On behalf of the Chairman and Committee I would like to take this opportunity of thanking all workers for the Torquay Clinic for their willing and efficient service. D.B. MOTTRAM, Hon. Sec. 30 292/841.51/2/2